ANDROID-BASED GOOGLE TRANSLATE TRAINING FOR MATHEMATICS SUBJECT TEACHERS' DELIBERATIONS IN UNDERSTANDING HIGH-LEVEL REASONING TEST ITEM IN SOPPENG REGENCY, SOUTH SULAWESI - Rukli Rukli; Syamsiarna Nappu (Pusat Pengembangan dan Kajian Sarana dan Prasarana Pendidikan (P2K Sarprasdik), 2022)
English is the social language of the world, but teachers still have limitations, especially in translating English texts. This service aims to provide counselling, training and mentoring for groups of teachers involved in consulting mathematics teachers. The activity involved 28 mathematics teachers as delegates from each school or madrasa in Soppeng Regency. Each stage is carried out pre-test and post-test. Data analysis used percentages and paired t-tests with a significance level of 0.05. The results of the service showed that 1) participants' body movements before and after the activity increased in a better direction, 2) participants' understanding of translating texts in the form of words, syllables, sentences and paragraphs increased, 3) participants' skills in translating English texts increased by an average of 80%, 4) there was a significant difference in improvement before and after counselling, training, and teacher assistance in translating high-level reasoning English text sources. Therefore, improving the ability and skills to translate English texts can use three stages: counselling, training and mentoring using text sources from international journals or international standard math problems